Composition of TWIST1 dimers regulates fibroblast activation and tissue fibrosis - Palumbo-Zerr, Katrin; Soare, Alina; Zerr, Pawel; Liebl, Andrea; Mancuso, Rossella; Tomcik, Michal; Sumova, Barbora; Dees, Clara; Chen, Chih-Wei; Wohlfahrt, Thomas; Mallano, Tatjana; Distler, Alfiya; et al. (Annals of the Rheumatic Diseases, 2017)
TWIST1 is a member of the class B of basic helix-loop-helix transcription factors that regulates cell lineage determination and differentiation and has been implicated in epithelial-to-mesenchymal transition. Here, we aimed to investigate the role of TWIST1 for the activation of resident fibroblasts in systemic sclerosis (SSc).The expression of Twist1 in fibroblasts was modulated by forced overexpression or siRNA-mediated knockdown. Interaction of Twist1, E12 and inhibitor Of differentiation (Id) was analysed by co-immunoprecipitation. The role of Twist1 in vivo was evaluated using inducible, conditional knockout mice with either ubiquitous or fibroblast-specific depletion of Twist1. Mice were either challenged with bleomycin or overexpressing a constitutively active transforming growth factor (TGF)? receptor I.The expression of TWIST1 was increased in fibroblasts in fibrotic human and murine skin in a TGF?/SMAD3-dependent manner. TWIST1 in turn enhanced TGF?-induced fibroblast activation in a p38-dependent manner. The stimulatory effects of TWIST1 on resident fibroblasts were mediated by TWIST1 homodimers. TGF? promotes the formation of TWIST1 homodimers by upregulation of TWIST1 and by induction of inhibitor of DNA-binding proteins, which have high affinity for E12/E47 and compete against TWIST1 for E12/E47 binding. Mice with selective depletion of Twist1 in fibroblasts are protected from experimental skin fibrosis in different murine models to a comparable degree as mice with ubiquitous depletion of Twist1.Our data identify TWIST1 as a central pro-fibrotic factor in SSc, which facilitates fibroblast activation by amplifying TGF? signalling. Targeting of TWIST1 may thus be a novel approach to normalise aberrant TGF? signalling in SSc.
EVALuna2:13273

Gamma interferon-induced guanylate binding protein 1 is a novel actin cytoskeleton remodeling factor - Ostler, Nicole; Britzen-Laurent, Nathalie; Liebl, Andrea; Naschberger, Elisabeth; Lochnit, Guenter; Ostler, Markus; Forster, Florian; Kunzelmann, Peter; Ince, Semra; Supper, Verena; Praefcke, Gerrit J. K.; Schubert, Dirk W.; et al. (Molecular and Cellular Biology, 2014)
Gamma interferon (IFN-?) regulates immune defenses against viruses, intracellular pathogens, and tumors by modulating cell proliferation, migration, invasion, and vesicle trafficking processes. The large GTPase guanylate binding protein 1 (GBP-1) is among the cellular proteins that is the most abundantly induced by IFN-? and mediates its cell biologic effects. As yet, the molecular mechanisms of action of GBP-1 remain unknown. Applying an interaction proteomics approach, we identified actin as a strong and specific binding partner of GBP-1. Furthermore, GBP-1 colocalized with actin at the subcellular level and was both necessary and sufficient for the extensive remodeling of the fibrous actin structure observed in IFN-?-exposed cells. These effects were dependent on the oligomerization and the GTPase activity of GBP-1. Purified GBP-1 and actin bound to each other, and this interaction was sufficient to impair the formation of actin filaments in vitro, as demonstrated by atomic force microscopy, dynamic light scattering, and fluorescence-monitored polymerization. Cosedimentation and band shift analyses demonstrated that GBP-1 binds robustly to globular actin and slightly to filamentous actin. This indicated that GBP-1 may induce actin remodeling via globular actin sequestering and/or filament capping. These results establish GBP-1 as a novel member within the family of actin-remodeling proteins specifically mediating IFN-?-dependent defense strategies.
EVALuna2:15143

Matricellular protein SPARCL1 regulates tumor microenvironment-dependent endothelial cell heterogeneity in colorectal carcinoma - Naschberger, Elisabeth; Liebl, Andrea; Schellerer, Vera; Schütz, Manuela; Britzen-Laurent, Nathalie; Kölbel, Patrick; Schaal, Ute; Haep, Lisa; Regensburger, Daniela; Wittmann, Thomas; Klein-Hitpass, Ludger; Rau, Tilman; et al. (Journal of Clinical Investigation, 2016)
Different tumor microenvironments (TMEs) induce stromal cell plasticity that affects tumorigenesis. The impact of TME-dependent heterogeneity of tumor endothelial cells (TECs) on tumorigenesis is unclear. Here, we isolated pure TECs from human colorectal carcinomas (CRCs) that exhibited TMEs with either improved (Th1-TME CRCs) or worse clinical prognosis (control-TME CRCs). Transcriptome analyses identified markedly different gene clusters that reflected the tumorigenic and angiogenic activities of the respective TMEs. The gene encoding the matricellular protein SPARCL1 was most strongly upregulated in Th1-TME TECs. It was also highly expressed in ECs in healthy colon tissues and Th1-TME CRCs but low in control-TME CRCs. In vitro, SPARCL1 expression was induced in confluent, quiescent ECs and functionally contributed to EC quiescence by inhibiting proliferation, migration, and sprouting, whereas siRNA-mediated knockdown increased sprouting. In human CRC tissues and mouse models, vessels with SPARCL1 expression were larger and more densely covered by mural cells. SPARCL1 secretion from quiescent ECs inhibited mural cell migration, which likely led to stabilized mural cell coverage of mature vessels. Together, these findings demonstrate TME-dependent intertumoral TEC heterogeneity in CRC. They further indicate that TEC heterogeneity is regulated by SPARCL1, which promotes the cell quiescence and vessel homeostasis contributing to the favorable prognoses associated with Th1-TME CRCs.
EVALuna2:6838

N-glycosylation Regulates Intrinsic IFN-γ Resistance in Colorectal Cancer: Implications for Immunotherapy - Krug, Julia; Rodrian, Gabriele; Petter, Katja; Yang, Hai; Khoziainova, Svetlana; Guo, Wei; Benard, Alan; Merkel, Susanne; Gellert, Susan; Maschauer, Simone; Spermann, Monika; Waldner, Maximilian; et al. (Gastroenterology, 2023)
Background & AIMS: Advanced colorectal carcinoma (CRC) is characterized by a high frequency of primary immune evasion and refractoriness to immunotherapy. Given the importance of interferon (IFN)-γ in CRC immunosurveillance, we investigated whether and how acquired IFN-γ resistance in tumor cells would promote tumor growth, and whether IFN-γ sensitivity could be restored. Methods: Spontaneous and colitis-associated CRC development was induced in mice with a specific IFN-γ pathway inhibition in intestinal epithelial cells. The influence of IFN-γ pathway gene status and expression on survival was assessed in patients with CRC. The mechanisms underlying IFN-γ resistance were investigated in CRC cell lines. Results: The conditional knockout of the IFN-γ receptor in intestinal epithelial cells enhanced spontaneous and colitis-associated colon tumorigenesis in mice, and the loss of IFN-γ receptor α (IFNγRα) expression by tumor cells predicted poor prognosis in patients with CRC. IFNγRα expression was repressed in human CRC cells through changes in N-glycosylation, which decreased protein stability via proteasome-dependent degradation, inhibiting IFNγR-signaling. Downregulation of the bisecting N-acetylglucosaminyltransferase III (MGAT3) expression was associated with IFN-γ resistance in all IFN-γ–resistant cells, and highly correlated with low IFNγRα expression in CRC tissues. Both ectopic and pharmacological reconstitution of MGAT3 expression with all-trans retinoic acid increased bisecting N-glycosylation, as well as IFNγRα protein stability and signaling. Conclusions: Together, our results demonstrated that tumor-associated changes in N-glycosylation destabilize IFNγRα, causing IFN-γ resistance in CRC. IFN-γ sensitivity could be reestablished through the increase in MGAT3 expression, notably via all-trans retinoic acid treatment, providing new prospects for the treatment of immune-resistant CRC.
CRIS-Team Scopus Importer:2023-02-10
Keywords: Colon Cancer; IFNGR1; Immune Evasion